Methods engineering and standards setting finishing section James Hardie Phil., Inc. - Barreto, Ma. Cristina; Enderez, Anatolio; Ramirez, Paul Levi. (Diliman, Quezon City College of Engineering, 1987)
James Hardie Philippines Incorporated (JHPI), is a multinational company and one of the world leaders in the manufacture of Fiber Cement Building Boards, with the brand Hardiflex. JHPI was studied for a period of two weeks, with six days of actual plant visits. The study centered on methods improvement and standards setting in the Finishing Section of the JHPI Plant in Cabuyao, Laguna. Time measurements, on-site observations of the work processes, interviews with the workers, team leaders and management were conducted, utilizing the various tools and problem solving techniques of Methods Engineering. The group was able to identify several problem areas within the Finishing Section of the Plant. Lack of standardized procedures in performing most of the work and processes in the Section results to an inefficient Finishing Process. A closer scrutiny of the problem of non-standardization revealed the following problem areas : frequent machine breakdown, machines not being able to maximize their design capacities, significant amount of forklift delay time, bottleneck operations in the inspection and break-up operations, significant volume of temporary and non-value adding storages, most operations are performed in a highly randomized manner, workers are tasked to perform jobs other than their own. For each of the problem areas stated, alternative solutions are presented, accompanied by corresponding evaluations focusing on improvements in quality, consistency and economy. Alternatives found to provide the greatest increases in the said criteria are recommended for implementation. An implementation plan and strategy was proposed so as to serve as guidelines for the management of James Hardie Philippines, Inc. in case they prefer to realize the benefits of the methods improvements, recommendations and standardizations that the Study presents.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis